Pelaksanaan Fungsi Badan Permusyawaratan Desa dalam Pembentukan Peraturan di Desa Peguyangan Kangin - Ida Ayu Putu Widiati; I Made Gede Bagus Anggara; Luh Putu Suryani (Warmadewa Press, 2025)
Village Regulations are the result of a legal process at the village level that is authorized by the Village Head together with the Village Consultative Body. The Village Consultative Body acts as a liaison between the Village Head and the Village community. This research aims to explore the implementation of the functions of the Village Consultative Body in the formation of Village Regulations in Peguyangan Kangin Village and identify obstacles or barriers faced by the Village Consultative Body in the process. The research method used is an empirical legal method. The results showed that although the Village Consultative Body has a function to take and propose ideas from the community, its implementation has not been optimal because there are still obstacles, such as community disapproval of the Village Regulations made. Efforts made include socializing the formation of Village Regulations to the community. Therefore, the Village Consultative Body should become more proactive in carrying out their roles and functions.